Therapeutic Impact of Plant-Derived Extracts and their Silver Nanoparticle-Loaded Extracts on the Zoonotic Parasite Hymenolepis Nana Infection - Wesam M. A. Elgendy; Hany M. El-Wahsh; Doaa Naguib; Rasha A. Elmahy; Suzan Awad AbdelGhany Morsy; Ashraf Fawzy Mosa Ahmed; Marim Fayz Abdow; Nabeel Hussain Alhussainy; Faten Abdullah Al Braikan; Ahmed Bendari; Akram Abu-Okail; Amira Mohamed AbdelHady Elhosyni (Acta Parasitologica, 2026)

Effects of a Magnetic Field on Surface and Subsurface Drip Irrigation Water, Tomato Plants and Desert Sandy Soil Characteristics - Ahmed A. Al‐Othman; Doaa M. El‐Shinawy; Awad Ali Tayoush Oraiath; Abdallah Elshawadfy Elwakeel; Ahmed Z. Dewidar; Ahmed Elbeltagi; A. H. Hamza (Irrigation and Drainage, 2026)
This study, conducted in Shosha, Minia, Egypt, aimed to evaluate the effects of magnetically treated saline groundwater on both soil characteristics and the performance of tomato crops grown in arid sandy soils. The influence of magnetic fields on water quality was first assessed to determine its suitability for irrigation. Subsequently, the combined effects of MWT with different irrigation methods—namely, surface drip irrigation (SDI) and subsurface drip irrigation (SSDI)—as well as system design types (closed vs. open systems), were examined to understand their impact on soil health and chemical properties under saline conditions. Magnetic treatment significantly improved water quality by reducing sodium and chloride accumulation in the root zone and decreasing the Na/Cl ratio from 1.07 to 0.98. This facilitated salt leaching and reduced plant salt stress. Treated water also lowered soil electrical conductivity (EC) and soluble ion concentrations while increasing soil moisture retention and field capacity. SSDI with magnetised water achieved a wetted soil volume of 94,500 cm 3 —vastly greater than 6720 cm 3 under unmagnetised open SDI. Emitter clogging ratio (ECR) was reduced from 12% to 5%, improving system reliability. Application efficiency rose from 89% to 97%, and emission uniformity improved from 90% to 96%.

Lectin Gene Families in Three Phaseolus Species: Genome-Wide Identification, Evolutionary Analysis, Pleiotropic Effect, and Regulation Under Multiple Stress Conditions - Makarim Elfadil M. Osman; Amina I. Dirar; Mohanad A. Ibrahim; Rieham Sallah H. Osman; Doaa Awad Yassin Ali; Somia Elmosharaf Elrayah Yousif; Hana Badreldin Mohamed Abakar; Nada Hassan M. Haj; Emadeldin Hassan E. Konozy (Journal of Molecular Evolution, 2026)

Melatonin and Strigolactone Combined Application Mitigate Salinity Stress Through Modulation of Antioxidants Defense Mechanism, Osmotic Adjustment and Ions Homeostasis in Maize Seedlings - Salman Aloufi; Basmah M. Alharbi; Abdul Sattar; Zahid Khorshid Abbas; Fahad Mohammed Alzuaibr; Nadi Awad Al-Harbi; Mohammed Alqurashi; Doaa Bahaa Eldin Darwish (Journal of Soil Science and Plant Nutrition, 2025)

Torsional irregularity of NSC and HSC asymmetric multistory 3-D buildings - Ahmed M. Yousef; Ahmed A. Ghaleb; Doaa M. Awad; Mohamed Ghannam (Innovative Infrastructure Solutions, 2025)
The reliability of the criteria adopted by the seismic codes in the United States (ASCE/SEI-7-16), in Europe (EC-8) and Egypt (ECP201-2012), that are used in distinguish torsionally irregular from torsionally regular Normal-Strength Concrete (NSC) and High-Strength Concrete (HSC) multistory 3-D buildings have been studied. The Static Equivalent Lateral Force (SELF) methods used by these codes for predicting the torsional moments have been examined when applied to NSCand HSCtorsionally asymmetric multistory buildings. Finite element model has been used to solve the nonlinear equations of motions for two multistory buildings examples with different eccentricity (e equal to 0.10L i , 0.15L i and 0.20L i ) and constructed from NSC ( $$f_{c}^{′ }$$ f c ′ = 25 N/mm 2 ), HSC( $$f_{c}^{′ }$$ f c ′ up to 75 N/mm 2 ) and VHSC ( $$f_{c}^{′ }$$ f c ′ up to 100 N/mm 2 ). Many different earthquake records have been used in the seismic analysis. The results showed that the criteria adopted by ASCE/SEI-7-16 so as to distinguish torsionally regular from torsionally irregular NSC, HSC and VHSC multistory buildings are the most reliable and more simple and accurate when compared with the methods adopted by EC-8 and ECP201-2012. The provisions of ECP201-2012 for determination of the torsional irregularity of a building depending on the calculated structural eccentricity (between C. M. and C. R.) may lead to unsafe results. Using the SELF methods of the studied seismic codes in predicting the torsional moments of some torsionally symmetrical and torsionally asymmetrical multistory buildings constructed from NSCand HSCmay lead to unsafe and unconservative predictions. The value of the accidental eccentricity adopted by the studied seismic codes underestimated the torsional moments predicted using SELF methods of the studied codes in some torsionally symmetrical and torsionally asymmetrical multistory buildings.

A deep deterministic policy gradient approach for optimizing feeding rates and water quality management in recirculating aquaculture systems - Wael M. Elmessery; Said Elshahat Abdallah; Awad Ali Tayoush Oraiath; Víctor Espinosa; Mohamed Fawzi Abdalshefie Abuhussein; Péter Szűcs; Mohamed Hamdy Eid; Doaa M. El-Shinawy; Huda Aljumayi; Samy F. Mahmoud; Abdallah Elshawadfy Elwakeel (Aquaculture International, 2025)
Optimizing feeding rates in recirculating aquaculture systems (RAS) is crucial for ensuring fish growth, health, and system efficiency. This research introduces a novel approach to RAS feeding control using a Deep Deterministic Policy Gradient (DDPG) reinforcement learning algorithm. The developed system integrates feeding rate optimization with comprehensive water quality management to improve overall performance and stability. The DDPG controller demonstrated superior tracking accuracy, reduced feed consumption, and improved operational stability compared to traditional control methods such as Model Predictive Control (MPC), PID, and Bang-Bang control. The learned policy-maintained feeding rates within optimal ranges while adapting to dynamic system requirements and environmental conditions. The integration of water quality monitoring and control further enhanced system stability, ensuring critical parameters remained within target ranges. Comparative analysis revealed the DDPG controller’s advantages in terms of faster recovery times after environmental perturbations, improved long-term stability, and significant economic benefits through reduced operational costs and increased efficiency. The robustness and adaptability of the system were validated through comprehensive testing under various fault conditions, growth phases, and system scales. The successful development and evaluation of the DDPG-based RAS feeding control system represents a significant advancement in aquaculture management. The demonstrated improvements in efficiency, stability, and economic performance establish the potential for this approach to revolutionize feeding practices in commercial RAS operations. Further research and development efforts can build upon these findings to advance the state-of-the-art in intelligent aquaculture management systems and promote the sustainability and profitability of the industry.

Application of Biostimulants Alleviated Drought Stress in Sugar Beet (Beta vulgaris L.) by Improving Oxidative Defense System, Osmolytes Accumulation and Root Yield - Abdul Sattar; Ahmed Abou El-Yazied; Basmah M. Alharbi; Hany G. Abd El-Gawad; Zahid Khorshid Abbas; Karima Mohamed El-Absy; Samy F. Mahmoud; Mohammed M. Althaqafi; Doaa Bahaa Eldin Darwish; Nadi Awad Al-Harbi; Qasim Ali; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Tyrosine Mitigated the Adversities of Drought Stress in Maize Seedlings through Modulation of Photosynthetic Performance and Antioxidants Defense Systems - Mohamed M. El-Mogy; Abdul Sattar; Qasim Ali; Basmah M. Alharbi; Zahid Khorshid Abbas; Siham M. AL-Balawi; Mohammed M Althaqafi; Nadi Awad Al-Harb; Salem Mesfir Al-Qahtani; Doaa Bahaa Eldin Darwish (Journal of Soil Science and Plant Nutrition, 2024)

The puzzling etiologies of transient black discoloration in Nile Tilapia (Oreochromis niloticus) intensively cultured under RAS system - Alaa Eldin Eissa; Marwa M. Attia; Rabia A. El Zlitne; Ayad A. Magdy; Asmaa Edrees; Mahmoud S. Sharaf; Abeer E. Mahmoud; Awad A. Abdelbaky; Rehab R. Abd ElMaged; Elshaimaa Ismael; Rehab A. Qorany; Doaa F. El Moghazi; et al. (Aquaculture International, 2024)
The aim of this study is to identify the hidden etiologies of the black chromo-shifting transient phenomenon affecting Nile tilapia, Oreochromis niloticus , farmed in RAS-controlled ponds together with the assessment of the immunological reaction against the chronic irritating effects of the invasive agent. A total of 100 Nile Tilapia were collected from a private farm at Kafrelsheikh Province, located on the northern side of the Egyptian Nile Delta. The clinical history of the affected fish farm showed an unknown chromo-shifting phenomenon where tilapias were exhibiting severe black skin coloration, which gradually disappeared after removal from the tank’s water. A comprehensive gross examination of the collected fish; including parasitological examination of skin and gill scraps, was performed. Blood biochemical testing was performed on the infested blackish O. niloticus and control non-infested fish. The current study showed that the monogenean parasite, Gyrodactylus cichlidarum , was the abundant parasite detected in the infested fish leading to abnormal black discoloration of skin and disruption of the immune system represented by significant increase of cortisol levels, lysozyme activity and different liver enzymes compared to the control. Treatment trials have been applied with moderate degrees of success, where the monogenean count was sharply decreased, and the normal skin color was remarkably restored, at the end of day 14 post-treatment. A triple treatment plan was initiated through 7 days’ application of 0.7 g/m 3 copper sulfates pentahydrate preceded by 1.5 ml/m 3 hydrogen peroxide 40% solution for the same period. One day after the end of the initial treatment, a maintenance dosage of 0.095 ml/m 3 of glutaraldehyde (15%)/quaternary ammonium compounds (QACs) mixture was administered for 3 days. As a supportive/immune-stimulant regimen, a weekly dosage of vitamin C (0.45 g g/m 3 ) and Saccharomyces cerevisiae (0.45 g/m 3 ) was added into the tank’s water to improve the general fish health.

Fe-Co spinel oxides supported UiO-66-NH2 derived zirconia/ N-dopped porous hollow carbon as an efficient oxygen reduction reaction electrocatalyst - Soliman Gamal; Doaa A. Kospa; Mahmoud M. Kaid; S.A. El-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Journal of Environmental Chemical Engineering, 2023)

Therapeutic effect of dithiophenolato chitosan nanocomposites against carbon tetrachloride-induced hepatotoxicity in rats - Nadia Z. Shaban; Ahmed M. Aboelsaad; Doaa Awad; Shaymaa A. Abdulmalek; Shaban Y. Shaban (Environmental Science and Pollution Research, 2022)

Effect of some pyrimidine compounds on rat brain monoamine oxidase-B in vitro - Nadia Z. Shaban; Mamdouh S. Masoud; Mai A. Mawlawi; Doaa Awad; Omayma M. Sadek (Journal of Physiology and Biochemistry, 2012)